(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Myths help us appreciate their traditions and customs. The western myths are mainly drawn from Greek and Roman myths. In India, we have our own Ramayana and Mahabharata, Vedic stories, Upanishads, etc., which have been made accessible to us since our early days. The dilemma is that we do not really comprehend them, since the whole tale is not told but just some sections. Indian myths are predominantly patriarchal and women assume marginal positions, while the epic core is more about the behavior of these women. Modern mythological myths give a different impression of the characters of the women of these epics. Amish Tripathi’s Ram Chandra Sequence is such a strong revisit to Ramayana. Scion of Ikshvaku, which deals with the past of Ram, and Sita Warrior of Mithila, who deals with the tale of Sita, will be the first novel in the book. Amish plans to compose the series in the tradition of multilinear narrative. These two books are accompanied by additional books that combine the tales of the main characters. The aim of this paper is to examine the analysis of Unostentatious vibrant Sita in Amish Tripathi’s novel Sita warrior of Mithila.